Intravascular Large B-Cell Lymphoma - Loukhnati, Mehdi; Lahlimi, Fatima Ezzahra; Tazi, Illias (Case Reports in Hematology, 2023)
Intravascular large B-cell lymphoma (IVBCL) is a very rare and aggressive subtype of extranodal diffuse large B-cell lymphoma (DLBCL) involving the growth of lymphoma cells within blood vessels of all organ types. We present the case of a 55-year-old North-African man with no prior history of neoplastic disease presenting with weight loss and an isolated splenomegaly. Investigations led to the diagnosis of this disease. To the best of our knowledge, this is the first case recorded in Africa. Through this article, we discuss this case and outline the common presentation, paraclinical investigations, and treatment options of IVBCL.